UK APAP R-Matrix Electron-Impact Excitation Cross-Sections for Modelling Laboratory and Astrophysical Plasma - Giulio Del Zanna; Guiyun Liang; Junjie Mao; Nigel R. Badnell (Atoms)
Systematic R-matrix calculations of electron-impact excitation for ions of astrophysical interest have been performed since 2007 for many iso-electronic sequences as part of the UK Atomic Process for Astrophysical Plasma (APAP) network. Rate coefficients for Maxwellian electron distributions have been provided and used extensively in the literature and many databases for astrophysics. Here, we provide averaged collision strengths to be used to model plasma where electrons are non-Maxwellian, which often occurs in laboratory and astrophysical plasma. We also provide many new Maxwellian-averaged collision strengths, which include important corrections to the published values. Recently, we made available the H- and He-like collision strengths. Here, we provide data for ions of the Li-, Be-, B-, C-, N-, O-, Ne-, Na-, and Mg-like sequences.